Analysis of local forage potential under ruminant - palm plantation integration system in Mandau District, Bengkalis Regency of Riau Province - Dedi Ramdani; Luki Abdullah; Nur Rochmah Kumalasari (Buletin Ilmu Makanan Ternak, 2017)
Palm plantations have a huge potential to support ruminant farm through forage supplies under palm trees. The aim of this research was to obtained information about forage local potential production under palm plantations in term on availability forage species, production, botanical composition and nutrition composition. Data collection was conducted in Mandau distric, Bengkalis regency, Riau province, from March to July 2015. We focussed on three villages with the widest area of palm plantation Petani Village, Sebangar Village and Bumbung Village. Plot sampling classified by palm trees age 3 years, 9 years and 15 years. The research resulted we found 20 forage specieses 1in palm plantation. Forage botanical composition on palm plantation 3 years dominated by Panicum anceps about 62,35% (Bumbung village), 50,20% (Petani village) and 56,59% (Sebangar village), while the age 9 and 15 years dominated by Paspalum conjugatum. Forage species dominate at all village an age are Paspalum conjugatum dan Ageratum conyzoides. The highest wet weight production found in 3 years age palm plantation, are 11.906,29 kg ha-1 (Bumbung village), 11.628,96 kg ha-1 (Sebangar village) dan 5.775,63 kg ha-1 (`Petani village). Nutrision composition was convert to wet material percent. The Sebangar village on 3 years age have highest dry weigh 35,43%. The highest crude protein on 9 years age of Petani village (3,79%). The highest crude fat on 3 years age of bumbung village (1,07%) and the highest fiber crude on 3 years age of Petani village (11,15%).Keywords : Forage, palm, production, ruminant, Riau